'I don't have to explain myself': using open groups to mobilise peer support in palliative care. Issue 2 (1st September 2011) - Cullen, Anne; Nolan, Steve; Sandford, Mo
Abstract : Model: Over the last 2 years members of a hospice social work, bereavement and chaplaincy service have piloted the use of semi-structured, facilitated open groups for day hospice patients, carers and bereavement service users. The approach is based on slow-open homogeneous group work model. Rationale: The approach developed initially as an operational response to the needs of a number of Carers' Group users who were inappropriately returning to the group after the death of the person they had cared for. Team members observed that those who returned were seeking a continuing connection with the hospice and staff that had provided a safe, 'holding' environment. In addition, staff identified that any support group would need to be user-led, inclusive and flexible. The evident success of this responsive model of semi-structured, facilitated open group work lent itself to other groups of varying size, and the model has been used with several initiatives, including weekly day hospice patient groups and monthly family bereavement groups, which attract 25–30 children and adults. Feedback: Evaluations by participants of all the groups indicate that this approach is well attuned to the needs of palliative care services users. A further unanticipated benefit is that the model provides the opportunity for skill sharing within the multi-disciplinary team, including salaried staff and volunteers. Focus of presentation: This presentation, based on a rigorous service evaluation, outlines the development of the model as a response to user needs; it describes the principles on which the model has been established; and it critically appraises the strengths and weaknesses of the model through user feedback and staff reflections.